Evolutionary Equilibrium in Stochastic Contests - Entry, Effort, and Overdissipation - Gu, Yiguan; Hehenkamp, Burkhard; Leininger, Wolfgang

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja
In actual school choice applications the theoretical underpinnings of the Boston School Choice Mechanism (BM) (complete information and rationality of the agents) are often not given. We analyze the actual behavior of agents in such a matching mechanism, using data from the matching mechanism currently used in a clearinghouse at a faculty of Business Administration and Economics at a German university, where a variant of the BM is used, and supplement this data with data generated in a survey among students who participated in the clearinghouse. We find that under the current mechanism over 70% of students act strategically. Controlling for students' limited information, we find that they do act rationally in their decision to act strategically. While students thus seem to react to the incentives to act strategically under the BM, they do not seem to be able to use this to their own advantage. However, those students acting in line with their beliefs manage a significantly better personal outcome than those who do not. We also run simulations by using a variant of the deferred acceptance algorithm, adapted to our situation, to show that the use of a different algorithm may be to the students' advantage.

Innovations, growth and participation in advanced economies - a review of major concepts and findings - Gries, T.; Grundmann, R.; Palnau, Irene; Redlin, Margarete (International Economics and Economic Policy)

Does Price Framing Affect the Consumer Price Sensitivity of Health Plan Choice? - Schmitz, Hendrik; Ziebarth, Nicolas R. (Journal of Human Resources)

Informal Care and Long-term Labor Market Outcomes - Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)

On the interdependence of ambulatory and hospital care in the German health system - Büyükdurmus, Tugba; Kopetsch, Thomas; Schmitz, Hendrik; Tauchmann, Harald (Health Economics Review)

Technology diffusion, international integration and participation in developing economies - a review of major concepts and findings - Gries, Thomas; Grundmann, R.; Palnau, Irene; Redlin, Margarete (International Economics and Economic Policy)

Towards an Economic Theory of Destabilization War - Gries, Thomas; Haake, Claus-Jochen (Peace Economics, Peace Science and Public Policy)

Sustainability of coalitional equilibria within repeated tax competition - Brangewitz, Sonja; Brockhoff, Sarah (European Journal of Political Economy)

Explaining inter-provincial migration in China - Gries, Thomas; Kraft, Manfred; Simon, Manuel (Papers in Regional Science)

Towards an Economic Theory of Destabilization War - Gries, Thomas; Haake, Claus-Jochen (Peace Economics and Peace Science)

The Entrepreneurship Beveridge Curve - Gries, Thomas; Jungblut, Stefan; Naudé, Wim (International Journal of Economic Theory)

Stackelberg Competition among Intermediaries in a Differentiated Duopoly with Product Innovation - Manegold, Jochen
On an intermediate goods market we consider vertical and horizontal product differentiation and analyze the impact of simultaneous competition for resources and the demand of customers on the market outcome. Asymmetries between intermediaries may arise due to distinct product qualities as well as by reasons of different production technologies. The intermediaries compete on the output market by choosing production quantities sequentially and for the supplies of a monopolistic input supplier on the input market. It turns out that there exist differences in product quality and productivities such that an intermediary being the Stackelberg leader has no incentive to procure inputs, whereas in the role of the Stackelberg follower will participate in the market. Moreover, we find that given an intermediary is more competitive, his equilibrium output quantity is higher when being the leader than when being the follower. Interestingly, if the intermediary is less competitive and goods are complements, there may exist asymmetries such that an intermediary being in the position of the Stackelberg follower offers higher output quantities in equilibrium than when being in the position of the Stackelberg leader.
Keywords: Input Market; Product Quality; Quantity Competition; Stackelberg Competition; Product Innovation

Reanalyzing Zero Returns to Education in Germany - Kamhöfer, Daniel A.; Schmitz, Hendrik (Journal of Applied Econometrics)

Competition of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen (Theoretical Economics Letters)
On an intermediate goods market with asymmetric production technologies as well as vertical and horizontal product differentiation we analyze the influence of simultaneous competition for resources and customers. The intermediaries face either price or quantity competition on the output market and a monopolistic, strategically acting supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Moreover, the well-known welfare advantage of price competition can in general be no longer confirmed in our model with an endogenous input market and asymmetric intermediaries.

Strategic Network Disruption and Defense - Hoyer, Britta; De Jaegher, Kris (Journal of Public Economic Theory)
We study a game between a network designer, who uses costly links to connect nodes in a network, and a network disruptor who tries to disrupt the resulting network as much as possible by deleting either nodes or links. For low linking costs networks with all nodes in symmetric positions are a best response of the designer under both link deletion and node deletion. For high linking costs the designer builds a star network under link deletion, but for node deletion excludes some nodes from the network to build a smaller but stronger network. For intermediate linking costs the designer again builds a symmetric network under node deletion but a star‐like network with weak spots under link deletion.

By-product mutualism and the ambiguous effects of harsher environments – A game-theoretic model - De Jaegher, Kris; Hoyer, Britta (Journal of Theoretical Biology)
We construct two-player two-strategy game-theoretic models of by-product mutualism, where our focus lies on the way in which the probability of cooperation among players is affected by the degree of adversity facing the players. In our first model, cooperation consists of the production of a public good, and adversity is linked to the degree of complementarity of the players׳ efforts in producing the public good. In our second model, cooperation consists of the defense of a public, and/or a private good with by-product benefits, and adversity is measured by the number of random attacks (e.g., by a predator) facing the players. In both of these models, our analysis confirms the existence of the so-called boomerang effect, which states that in a harsh environment, the individual player has few incentives to unilaterally defect in a situation of joint cooperation. Focusing on such an effect in isolation leads to the "common-enemy" hypothesis that a larger degree of adversity increases the probability of cooperation. Yet, we also find that a sucker effect may simultaneously exist, which says that in a harsh environment, the individual player has few incentives to unilaterally cooperate in a situation of joint defection. Looked at in isolation, the sucker effect leads to the competing hypothesis that a larger degree of adversity decreases the probability of cooperation. Our analysis predicts circumstances in which the "common enemy" hypothesis prevails, and circumstances in which the competing hypothesis prevails.

Do talented women shy away from competition? - Hoyer, Britta; van Huizen, Tomas; Keijzer, Linda; Rezai Khavas, Tahere; Rosenkranz, Stephanie
We study the willingness to compete in a cognitive task among an entire cohort of fresh man business and economics students. Combining data from a lab-in-thefield experiment with university admissions data, we trace the gender gap in competitiveness at different levels of high school performance. Our results confirm that, on average, men choose to compete more often. The gender gap disappears, however, among students with above average high school performance. Female high school top performers are equally competitive as their male counterparts. In fact, the overall gender gap is entirely driven by the group of female high school underperformers who shied away from competition, even when they performed well in our task. Overall, our findings suggest that high school grades are more than just a signal of cognitive abilities, because they seem to influence the receivers selfperception of his or her performance in a competitive environment involved in later on in life.

An Economic Theory of 'Destabilization War' - Gries, Thomas; Haake, Claus-Jochen
While Islamic State is the most present example, it is a fact that in many places around the globe, throughout history initially small groups have tried to challenge and destabilize or even overthrow governments by means of terrorist and guerrilla strategies. Therefore, we answer two questions. Why does a small group of insurgents believe it can overthrow the government by turning violent, even if the government is clearly superior? And how does a conflict develop into terrorism, a guerilla war, or a major conventional civil war, or is resolved peacefully? We develop a formal model for rebels and government and derive optimal choices. Further, we focus on three elements as important ingredients of a "destabilization war". All three of these - large random events, time preference (which we relate to ideology), and choice of duration of fight - are rarely considered in formal conflict theory. We can answer the above two questions using game theory analysis. First, insurgents rise up because they hope to destabilize through permanent challenging attacks. In this context, large randomness is an important ally of rebels. While each individual attack may have a low impact, at some point a large random event could lead to success. Hence, the duration of activities is a constitutive element of this kind of armed conflict. Patience (low time preference), which may reflect rebels' degree of ideological motivation, is crucial. Second, the mode of warfare or the conflict resolutions that develop are generally path-dependent and conditioned on the full set of options (including compromise). Various conditions (level of funding, ease of recruitment, access to weapons) influence different modes of warfare or a peaceful compromise in a complex way.
Keywords: terrorism; civil war; conflict duration; game theory; stochastic process; ideology

Quantile treatment effects of job loss on health - Schiele, Valentin; Schmitz, Hendrik (Journal of Health Economics)

Public reporting and the quality of care of German nursing homes - Herr, Annika; Nguyen, Thu-Van; Schmitz, Hendrik (Health Policy)

Determinants of regional variation in health expenditures in Germany - Göpffarth, Dirk; Kopetsch, Thomas; Schmitz, Hendrik (Health economics)

Health shocks and risk aversion - Decker, Simon; Schmitz, Hendrik (Journal of Health Economics)

Strategic Formation of Customer Relationship Networks - Brangewitz, Sonja; Haake, Claus-Jochen; Möhlmeier, Philipp
We analyze the stability of networks when two intermediaries strategically form costly links to customers. We interpret these links as customer relationships that enable trade to sell a product. Equilibrium prices and equilibrium quantities on the output as well as on the input market are determined endogenously for a given network of customer relationships. We investigate in how far the substitutability of the intermediaries' products and the costs of link formation influence the intermediaries' equilibrium profits and thus have an impact on the incentives to strategically form relationships to customers. For networks with three customers we characterize locally stable networks, in particular existence is guaranteed for any degree of substitutability. Moreover for the special cases of perfect complements, independent products and perfect substitutes, local stability coincides with the stronger concept of Nash stability. Additionally, for networks with n customers we analyze stability regions for selected networks and determine their limits when n goes to infinity. It turns out that the shape of the stability regions for those networks does not significantly change compared to a setting with a small number of customers.

Playing the Lottery or Dressing Up? A Model of Firm-Level Heterogeneity and the Decision to Export - Gries, Thomas; Naudé, Wim; Bilkic, Natascha (The Quarterly Review of Economics and Finance)

Changes of China’s agri-food exports to Germany caused by its accession to WTO and the 2008 financial crisis - Gries, Thomas; Feng, Yuanhua; Guo, Zhichao (China Agricultural Economic Review)

Sustaining Civil Peace: a configurational comparative analysis - Gries, Thomas; Palnau, Irene (Peace Economics, Peace Science and Public Policy)

Oppressive Governments, Dependence on the United States and Anti-American Terrorism - Gries, Thomas; Meierrieks, Daniel; Redlin, Margarete (Oxford Economic Papers)

Does technological change drive inclusive industrialization? - A review of major concepts and findings - Gries, Thomas; Grundmann, Rainer; Palnau, Irene; Redlin, Margarete

An iterative plug-in algorithm for realized kernels - Feng, Yuanhua; Zhou, Chen

Robust Equilibria in Location Games - Buechel, Berno; Röhl, Nils (European Journal of Operational Research)
In the framework of spatial competition, two or more players strategically choose a locationin order to attract consumers. It is assumed standardly that consumers with the same favorite location fully agree on the ranking of all possible locations. To investigate the necessity of this questionable and restrictive assumption, we model heterogeneity in consumers’ distance perceptions by individual edge lengths of a given graph. A proﬁle of location choices is called a “robust equilibrium” if it is a Nash equilibrium in several games which diﬀer only by the consumers’ perceptions of distances. For a ﬁnite number of players and any distribution of consumers, we provide a full characterization of all robust equilibria and derive structural conditions for their existence. Furthermore, we discuss whether the classical observations of minimal diﬀerentiation and ineﬃciency are robust phenomena. Thereby, we ﬁnd strong support for an old conjecture that in equilibrium ﬁrms form local clusters.

Rationalisierung vs. Rationierung Ist die Rationierung unvermeidbar? - Schmitz, Hendrik (Patient Gesundheitswesen – Mission 2030 Unsere gemeinsame Verantwortung die Zukunft zu gestalten)

Does technological change drive inclusive industrialization? A review of major concepts and findings - Gries, Thomas; Grundmann, Rainer; Palnau, Irene; Redlin, Margarete

Short-and medium-term effects of informal care provision on female caregivers’ health - Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)

Competitive outcomes and the inner core of NTU market games - Brangewitz, Sonja; Gamp, Jan-Philip (Economic Theory)

Trade and fertility in the developing world: the impact of trade and trade structure - Gries, Thomas; Grundmann, Rainer (Journal of Population Economics)

Household Savings and Productive Capital Formation in Rural Vietnam: Insurance vs. Social Network - Gries, Thomas; Dung, Ha Van (Modern Economy)

Low Carbon Economics - Theory and application - Gries, Thomas (Low Carbon Economics)

Too Much of a Good Thing? Welfare Consequences of Market Transparency - Gu, Yiquan; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics JITE)
This paper studies welfare consequences of consumer-side market transparency with endogenous entry of firms. Different from most studies, we consider the unique symmetric entry equilibrium, which is in mixed strategies. We identify two effects of market transparency on welfare: a competition effect and a novel market-structure effect. We show, surprisingly, that for almost all demand functions the negative market-structure effect eventually dominates the positive competition effect as the market becomes increasingly transparent. Consumer-side market transparency can therefore be socially excessive even without collusion. The only exception among commonly used demand functions is the set of constant demand functions.

Providing aid to repressive terrorist source countries does not make the U.S. any safer - Gries, Thomas; Meierriecks, Daniel; Redlin, Margarete

Maritime Piracy: Socio-Economic, Political, and Institutional Determinants - Gries, Thomas; Redlin, Margarete

A Crook is a Crook ... But is He Still a Crook Abroad? On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

Collective action and the common enemy effect - De Jaegher, Kris; Hoyer, Britta (Defence and Peace Economics)
How is collective defence by players affected when they face a threat from an intelligent attacker rather than a natural threat? This paper analyses this question using a game-theoretic model. Facing an intelligent attacker has an effect if players move first and visibly set their defence strategies, thereby exposing any players who do not defend, and if the attacker is, moreover, not able to commit to a random attack. Depending on the parameters of the game, the presence of an intelligent attacker either increases the probability that players jointly defend (where such joint defence either does or does not constitute a utilitarian optimum), or decreases the probability that players jointly defend (even though joint defence is a utilitarian optimum).

Kehrtwende in der Gesundheitspolitik - Unnötige Abkehr von einer erfolgreichen Reform zur Finanzierung der gesetzlichen Krankenversicherung - Schmitz, Hendrik; Augurzky, B.; Roppel, U. (RWI Position)

Testing the relationship between income inequality and life expectancy: A simple correction for the aggregation effect when using aggregated data - Mayrhofer, Thomas; Schmitz, Hendrik (Journal of Population Economics)

Broke, ill, and obese: is there an effect of household debt on health? - Keese, Matthias; Schmitz, Hendrik (Review of Income and Wealth)

Regional variation in the utilisation of ambulatory services in Germany - Kopetsch, Thomas; Schmitz, Hendrik (Health Economics)

Forschung und Lehre: Freund oder Feind? - Lück, Sonja (Die Betriebswirtschaft)

A Crook is a Crook … But is He Still a Crook Abroad? On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete (German Economic Review)

Oppressive governments, dependence on the USA, and anti-American terrorism - Gries, Thomas; Meierrieks, Daniel; Redlin, Margarete (Oxford Economic Papers)
Keywords: Economics and Econometrics